Odpowiedzi

2010-01-19T15:42:29+01:00
A ) ( - 2, 5 ) : 1 2/3 - 1,4 = (-5/2) x 3/5 - 1/4 = - 1 1/2 - 1/4 = - 1,5 - 1,4 = - 2,
b) 2,6 - 1/4 :[2-(-1,75 )] = b) 2,6 - 1/4 :[2 + 1,75 ] = 2,6 - 1/4 : 3,75 = 2,6 - 1/4 : 3 75/100 = 2,6 - 14 : 3 3/4 = 2,6 - 1/4 x 4/15 = 2 3/5 - 1/15 = 2 9/15 - 1/15 = 2 8/15
c) 1 2/5 x ( - 1 3/7 ) + [ 1+6 :(- 18) ] = 1 2/5 x ( - 1 3/7 ) +
[ 1 - 1/3 ] = 7/5 x ( - 10/7) + 2/3 = 2 + 2/3 = 2 2/3
d) [ - 2/3 - ( - 1.8 ): ( -1 1/5 )] :( - 1 /27 ) = [ - 2/3 - ( - 18/10 ) x ( - 5/6 )] x ( - 27 ) = [ - 2/3 - 1 1/2] x (-27) = [-4/6 - 1 3/6] x (-270 =
-2 1/6 x (- 27 ) = -13/6 x (-27) = 117/2 = 58,5
Najlepsza Odpowiedź!
2010-01-19T15:52:22+01:00
A ) ( - 2, 5 ) : 1 2/3 - 1,4 =(-5/2):5/3-1,4=
=(-5/2)*3/5-7/5=-3/2-7/5=-15/10-14/10=-29/10=-2 9/10
b) 2,6 - 1/4 :[2-(-1,75 )]=2,6-1/4:[3,75]=2 3/5-1/4:3 3/4=
=13/5-1/4:15/4=13/5-1/4*4/15=13/5-1/15=39/15-1/15=38/15=2 8/15

c) 1 2/5 * ( - 1 3/7 )+ [ 1+6 :(- 18) ] =7/5*(-10/7)+[1-1/3]=-2+2/3=-1 1/3
d) [ - 2/3 - ( - 1.8 ): ( -1 1/5 )] :( - 1 /27 ) =[-2/3-3/2]:(-1/27)=
=[-4/6-9/6]:(-1/27)=(-13/6)*(-27/1)=117/2=58 1/2